Genetic variability in pecan genotypes in Brazil - Schmidt de Souza, Rafaela; Martins, Carlos Roberto; Marques Castro, Caroline; Lobato Pinheiro Lima, Natércia; de Mello-Farias, Paulo Celso (Revista Ceres, 2023)
Pecan crops has been expanding in recent years, mainly in southern Brazil. Genotypes that compose Brazilian orchards come from the USA and from selections of plants made by Brazilian producers. This study aimed to characterize with microsatellite markers pecan cultivars registered for cultivation in Brazil, including some selections made in the country. It is important to know the genetic variability of the pecan tree, as it facilitates the identification of possible phytotechnical deficiencies due to the genetic similarity between the plants, in addition to helping in the conservation of the species, among other. Thirty-four, out of forty collected accessions, were genotyped with 11 selected SSR (Simple Sequence Repeats) loci. Twenty-four polymorphic alleles were identified. The genetic similarity matrix, based on the Jaccard coefficient, ranged from 0.125 to 1.0; general mean of similarity was 0.46. The cluster analysis, which was carried out by the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), classified pecan accessions into four main groups. Results showed that there is high genetic variability in germplasm evaluated, although some accessions may be duplicates.